IMPLEMENTASI STEGANOGRAFI DENGAN METODE END OF FILE PADA TEKS YANG TERENKRIPSI MENGGUNAKAN BLOCK CIPHER RIVEST CODE-6 KE DALAM CITRA - Andrew Chandra; Willy Sudiarto Raharjo; Junius Karel Tampubolon (Jurnal Informatika, 2015)
Datas or informations are very important assets nowdays, that is why we have to keep it safe so it will not fall into one who is do not have rights. There are several methods to maintain the confidentiality of datas/informations, which are cryptography and steganography. By using cryptographic Rivest Code-6 algorithm then the datas/informations is converted into a form that cannot be undestood, and then steganographic End of File algorithm the datas/informations is inserted into another media so that ordinaary people do not know the existence of the datas/informations. The results of this research tell that by using both algorithms the secret datas/informations can be hidden and read back properly. In addition there will be increase in file size reservoirs, where the increase in dependent on the size of the secret datas/informations and file size of the reservoir, while the length of the key to be isnerted into reservoir will remain  at 16 bytes.